DETERMINANTS OF EMPLOYEES’ VOLUNTARY TURNOVER INTENTION IN THE NIGERIAN BANKING INDUSTRY - B. M. Nwibere (American Journals, 2024)
This study investigates the determinants of employee voluntary turnover intention within the Nigerian banking industry. Adopting a cross-sectional survey approach and convenient sampling technique, data were collected from 270 randomly selected bank employees using questionnaires. Out of the 270 distributed questionnaires, 229 were retrieved and deemed suitable for analysis. The collected data were analysed using descriptive and inferential statistics. The findings revealed positive and statistically significant associations between favourable leadership style, favourable working conditions, favourable rewards and recognitions, favourable career advancement opportunities, and employees’ voluntary turnover intention. Specifically, democratic leadership styles, favourable working conditions, competitive rewards and recognitions, and ample career advancement opportunities were associated with lower employees’ voluntary turnover intentions, while autocratic leadership styles, adverse working conditions, unfavourable compensation, and limited career growth prospects were linked to higher employees’ voluntary turnover intentions. These results suggest that enhancing leadership practices, improving working conditions, revising rewards and recognitions structures, and promoting career advancement opportunities could help mitigate voluntary turnover intentions among employees in the Nigerian banking industry. The study underscores the importance of creating a positive work environment and implementing effective retention strategies within the Nigerian banking industry.
Keywords: Career Advancement Opportunity, Employees’ Voluntary Turnover Intentions, Leadership Style, Remuneration and Rewards, Working Conditions.